Box-Behnken design-based optimization of the Saccharification of primary paper-mill sludge as a renewable raw material for bioethanol production - Zambare, Vasudeo (MDPI, 2023)
In this study, the primary paper-mill sludge characterized as containing 51% glucan was used to optimize the enzymatic saccharification process for the production of bioethanol using a Box–Behnken design (BBD). Polyethylene glycol 4000 (PEG-4000) surfactant-assisted enzymatic saccharification of dried primary sludge (DPS) showed a 12.8% improvement in saccharification efficiency. There was a statistically significant effect of solid enzyme loading and saccharification time on the enzymatic saccharification of DPS at a 95% confidence level (p < 0.05). The optimum levels of 10.4% w/w DPS solid loading, 2.03% enzyme loading (10 FPU g/DPS), and 1% (w/w DPS) PEG-4000 loading for a saccharification efficiency of 57.66% were validated experimentally and found to be non-significant with regard to the lack of fit with the predicted saccharification efficiency of 56.76%. Furthermore, Saccharomyces cerevisiae fermented the saccharified sugars into ethanol (9.35 g/L) with a sugar-to-ethanol conversion yield of 91.6% compared with the theoretical maximum. Therefore, DPS is a more suitable renewable biomass for determining the presence of fermentable sugar and for the production of ethanol.